ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA KELAS VII SMP PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN LINEAR SATU VARIABEL DENGAN MENGGUNAKAN HANDS ON ATIVITY - Saragih, Derviana Agtria; Susilowaty, Nora (Jurnal Padegogik, 2024)
This research aims to describe students' creative thinking abilities in learning mathematics using Hands On Activity according to their level of ability, namely high, medium and low in the material of linear equations and inequalities in one variable. This type of research is descriptive research using a qualitative approach. The sample in this study was 29 students from class VII G of Parongpong State Middle School 1. The subjects in this research were 3 students. Data collection takes the form of written tests and interviews. The results of this research show that students at a high level of mathematical creative thinking ability are able to complete four creative thinking indicators. At a moderate level of mathematical ability, students can work on questions for only 3 indicators, namely fluency, flexibility and originality, but students experience difficulties on the elaboration indicator because when working on questions the subject makes mistakes in answering the questions. And at a low level of students' creative thinking abilities, students are only able to complete 1 indicator, namely originality, while the other 3 indicators, namely fluency, flexibility and elaboration, tend to be less able to answer questions well, even though the subject has tried his best to provide answers.